Bromatological and sensory analyses of a snack based corn flour and cassava root fortified with moringa to combat the malnutrition - Calderon Lopez, Juan Carlos; Bhaktikul, Kampanad (Bangladesh Journal of Botany, 2018)
This research details an effort to develop a nutritious snack that can alleviate, and combat problems associated with undernourishment product was developed using corn, cassava, and moringa (or teberinto). Two samples of the product were made, with 1 and 2% moringa, along with corn (60%) and cassava (39%) and were tested through a sensory analysis with 15 panelists. The better product was determined by applying the ANOVA to the results of the sensory analysis. The selected sample was the one containing 1% moringa. The product was subjected to microbiological tests for quality and bromatological tests and to ascertain its chemical composition. Results from both tests met the requirement of established standards. Three physicochemical determination (protein, moisture and ash) also provided favorable results. Thus combining these foods into a snack may contribute to mitigation of undernourishment.